Study of Credit Risk Identification Techniques Followed by Commercial Banks in Nepal - Kattel, Indra Kumar (Journal of Advanced Academic Research, 2017)
The main purpose of this study is to explore the current credit risk identification techniques used by Nepalese commercial banks. A questionnaire was developed and surveyed to 9 commercial banks operating in Nepal. This paper attempts to ascertain the perceptions of Nepalese bankers about the importance of credit identification techniques and the practice of various tools to identify the risk related with the borrowers. The result of the study indicates that the Nepalese bankers are aware of the importance of various techniques to effectively identify the risk level. Furthermore, the Nepalese commercial banks have used various techniques like interview, root cause effect, check list analysis, Strength, Weakness, Opportunity and Threat (SWOT) analysis, scenario analysis, expert judgment, simulation, stress testing etc. In addition, there was significant difference between all three categories of bank, namely State-Owned bank with Private Bank, State-Owned bank with Joint Venture Bank, and Joint Venture Bank with Private Bank in terms of tools and techniques used for credit risk identification.